2014
DOI: 10.1080/10941665.2013.866587
|View full text |Cite
|
Sign up to set email alerts
|

Visitor Books and Guest-generated Discourses of Hospitality: The Case of theHanok

Abstract: This study analyzes visitor book entries as cultural repositories of guest-generated hospitality discourses to understand how guests articulate/narrativize hospitality. Inquiry into visitor book entries offers insight into ways in which tourists render people and place intelligible. Utilizing textual analysis, this study examines discursive entries contained within visitor books displayed at a traditional South Korean hanok guesthouse/commercial home. The findings indicate that tourists' entries could be class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In commercial home enterprises (CHEs), customers have different expectations since the products and services offered differ from traditional hotels [30]. Owners of commercial homes "prioritize personal values, quality of life, and personal interactions above economic gains" and it is reflected in the dimensions valued by CHE guests [34] (p. 115).…”
Section: Satisfaction and Accommodation Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In commercial home enterprises (CHEs), customers have different expectations since the products and services offered differ from traditional hotels [30]. Owners of commercial homes "prioritize personal values, quality of life, and personal interactions above economic gains" and it is reflected in the dimensions valued by CHE guests [34] (p. 115).…”
Section: Satisfaction and Accommodation Modalitiesmentioning
confidence: 99%
“…In Korea, an endemic, traditional type of CHE accommodation exists called a "hanok", and it is popular for both domestic and international tourists. Hanok "literally means Korean house and it refers to an abode designed according to the traditional principles of Korean architectural culture" [34]. The traditional principles are known as pungsu-jiri (i.e., Feng Shui), and they direct how the traditional hanok accommodations are constructed [41].…”
Section: Satisfaction and Accommodation Modalitiesmentioning
confidence: 99%
“…Therefore, only economic entities were considered as focal agents of customer engagement. However, this study argues that interpersonal engagement also plays an important role in the customer engagement process, such as customer-customer engagement (Steele et al, 2017;Tussyadiah, Kausar, and Soesilo, 2018;Wei, Miao, and Huang, 2013;Zhang, Zhang, and Lu, 2019b), guest-host engagement (Choi, Buzinde, and Lee, 2015), customer-staff engagement (Huang and Choi, 2019) and tourist-community engagement (Sharma and Sarmah, 2019), etc.…”
Section: Conceptualisation Of Customer Engagementmentioning
confidence: 98%
“…Innovative research methods were shown in a few studies, such as Radic (2019) examined children's engagement with cruise travel through kids' drawing. Choi et al (2015) understood the engagement with guesthouse through visitors' books, and Muñoz, Liébana, and Hernández (2018) explored customers'engagement with hotels' advertisement through experiments based on eye-tracking technology. About model building, compared to SEM, PLS has the advantage of using nonnormal data, small sample sizes, and formative indicators (Hair, Sarstedt, Hopkins, and Kuppelwieser, 2014).…”
Section: Measurement Of Customer Engagementmentioning
confidence: 99%
See 1 more Smart Citation